Paediatric Buruli ulcer in Australia. (10th December 2019) - Walker, Georgia; Friedman, Deborah N; O'Brien, Matthew P; Cooper, Chris; McDonald, Anthony; Callan, Peter; O'Brien, Daniel P
Abstract : Aim: This study describes an Australian cohort of paediatric Buruli ulcer (BU) patients and compares them with adult BU patients. Methods: Analysis of a prospective cohort of all BU cases managed at Barwon Health, Victoria, from 1 January 1998 to 31 May 2018 was performed. Children were defined as ≤15 years of age. Results: A total of 565 patients were included: 52 (9.2%) children, 289 (51.2%) adults aged 16–64 years and 224 (39.6%) adults aged ≥65 years. Among children, half were female and the median age was 8.0 years (interquartile range 4.8–12.3 years). Six (11.5%) cases were diagnosed from 2001 to 2006, 14 (26.9%) from 2007 to 2012 and 32 (61.5%) from 2013 to 2018. Compared to adults, children had a significantly higher proportion of non‐ulcerative lesions (32.7%, P  < 0.001) and a higher proportion of severe lesions (26.9%, P  < 0.01). The median duration of symptoms prior to diagnosis was shorter for children compared with adults aged 16–64 years (42 vs. 56 days, P = 0.04). Children were significantly less likely to experience antibiotic complications (6.1%) compared with adults (20.6%, P  < 0.001), but had a significantly higher rate of paradoxical reactions (38.8%) compared with adults aged 16–64 (19.2%) ( P  < 0.001). Paradoxical reactions in children occurred significantly earlier than in adults (median 17 vs. 56 days, P  < 0.01). Cure rates were similarly high for children compared to adults treated with antibiotics alone or with antibiotics and surgery. Conclusions: Paediatric BU cases in Australia are increasing and represent an important but stable proportion of Australian BU cohorts. Compared with adults, there are significant differences in clinical presentation and treatment outcomes.